Geometallurgical characterisation of cassiterite at the groenfontein and zaaiplaats deposits in the Northern limb of the bushveld complex, South Africa - Nethononda, Tshilisanani Simon (My University, 2019)
Properties of the Groenfontein 227 KR and Zaaiplaats 223 KR farms are located within the Zaaiplaats tin mining district about 30 km north-west of Mokopane in Polokwane, South Africa. The present study evaluate the geometallurgical characteristics of the Groenfontein 227 KR and Zaaiplaats 223 KR farms, with the view of understanding the mineralogical constituent, grading analysis, grain size distribution, element deportment, and recovery of tin occurring within cassiterite ore. Within the properties of the Groenfontein and Zaaiplaats farms, the Renetype (Pty) Ltd obtained a prospecting licence in 2010, to explore for tin within cassiterite. The geometallurgical characteristics of the ore are the key to value realisation when applied to the optimisation of mining and plant processing, and the variability in the orebody enables optimum operational design and extraction methods that maximise value recovery. This has been accomplished by obtaining quantitative mineralogical information coupled with chemical assay, laboratory scale milling, and pilot-scale test-work by gravity spirals and shaking tables. The bulk samples and drilled core were collected from cassiterite ore on surface (old workings) at Groenfontein farm. The collected bulk samples were further coarsely crushed and estimated for mineral modal abundances, and then analysed for tin (Sn) concentrate. However, within the Zaaiplaats farm, samples were also collected from bulk samples, and further from tailings dump. The results from the studied samples indicate that impurities such quartz, feldspars, chlorite are the dominant mineralogical constituent within the bulk samples, drilled core and tailings. The calculated head grade of samples from drilled core, bulk samples within Groenfontein farm, and bulk samples and tailings from Zaaiplaats farm were 0.44 %, 0.12 %, 0.1 %, 0.13 %, and 0.13 % respectively. Shaking table results of the tailings at the upper-stream within the Zaaiplaats farm indicate that 50 % of Sn reported to the concentrate of 8 % and gravity tests at 0.2 % of Sn. In sample ZTD02, 40 % of Sn was recovered in the concentrate consisting of about 5 % mass and a final gravity tails of 0.22 % of Sn. In the drilling core sample within the Groenfontein farm, it was possible to upgrade the Sn concentrate to as high as 15 % into the concentrate, indicating that the drilling core sample was controlled by gravity concentration. Furthermore, in bulk samples from Groenfontein and Zaaiplaats farms, and drilled core from Groenfontein farm tin grade have a decreasing trend towards the coarse grained size fractions, while most of the tin mass is in the coarse fractions. Nonetheless, in bulk samples from Zaaiplaats farm the highest tin grade was 4887 ppm in the -425/+212 μm to -212/+106 μm size fraction. Based on core sample and ore dump, the study recommends a thorough evaluation based on the suitability of density medium separation prior to shaking table or spirals, by doing heavy liquid separation test-work at two different top sizes (8 mm and 5 mm) and two different densities (2.8 and 3). Keywords: Geometallurgy; Cassiterite; grading analysis; recovery
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of MSc. Johannesburg, 2019